Evaluation of tissue response to periodontal dressings: histological study in tooth sockets of rats - Hamata, Marcelo Matida; Saito, Célia Tomiko Matida Hamata [UNESP]; Murata, Sueli Satomi; Bernabé, Pedro Felício Estrada [UNESP]; Okamoto, Tetuo [UNESP]; Sundefeld, Maria Lucia Marçal Mazza [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2008)
Although the use of periodontal dressings is currently limited, there are some indications for their use. Selection of any material that will have direct contact with live tissues, such as periodontal dressings, should be careful in order to allow surgical wound healing. The aim of this study was to evaluate the intensity of inflammatory response and bone formation in tooth sockets of rats after implantation of three periodontal dressings. After removal of the right maxillary incisors of 84 male rats, each tooth socket received implantation of a polyethylene tube, 63 of which were filled with non-eugenol periodontal dressing and the remaining 21 tubes remained empty (control group). Histological evaluation assessed the intensity of inflammatory response and presence and location of bone tissue formation at postoperative periods of 7, 14 and 28 days. Statistical analysis was performed by the Kruskal-Wallis test at 5% significance level. Regarding the inflammatory infiltrate, at 28 days, there was statistically significant difference between one of periodontal dressings and control group (p<0.05). Analysis of postoperative periods, showed that the control group presented statistically significant reduction in the inflammatory infiltrate comparing the 14- and 28-day periods (p<0.05). Regarding bone tissue formation, there was difference in control group between the 7- and 28-day periods (p<0.05). Within the experimental conditions, it may be concluded that no differences were found in the inflammatory response among the groups at 7 and 14 days and that Voco pac™ dressing induced a more intensive inflammatory reaction at 28 days.
Keywords: Biocompatible materials; Dental materials; Periodontal dressings